2013
DOI: 10.5012/bkcs.2013.34.2.545
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Accurate Charges in Binding Affinity Calculations: A Case of Neuraminidase Series

Abstract: It has been shown that calculating atomic charges using quantum mechanical level theory greatly improves the accuracy of docking. A protocol was developed and shown to be effective. That this protocol works is just a manifestation of the fact that electrostatic interactions are important in protein-ligand binding. In order to investigate how the same protocol helps in prediction of binding affinities, we took a series of known cocrystal structures of influenza neuraminidase inhibitors with the receptor and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…Prior to molecular docking, the geometries of the compounds were quantum-mechanically (QM)-optimized using GAMESS-US [ 37 ] software (B3LYP/6-31G*). The optimized structures of the ligands were used with partial atomic charges derived from QM results [ 38 , 39 , 40 , 41 ] according to the Mulliken scheme [ 42 ] without torsion or any other degree of freedom for the ligands, which were frozen for molecular docking.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to molecular docking, the geometries of the compounds were quantum-mechanically (QM)-optimized using GAMESS-US [ 37 ] software (B3LYP/6-31G*). The optimized structures of the ligands were used with partial atomic charges derived from QM results [ 38 , 39 , 40 , 41 ] according to the Mulliken scheme [ 42 ] without torsion or any other degree of freedom for the ligands, which were frozen for molecular docking.…”
Section: Methodsmentioning
confidence: 99%
“…5,10 The correlation with experimental binding affinities was considerably improved with QPLD compared to Glide SP/XP. 31 Hence, the obtained better posed seed structures in RRD were further investigated through quantum-polarized ligand docking (QPLD) using Q-Site module at the B3LYP/6-31G* level, which yield excellent results for atomization energies and transition states in a wide range of chemical systems. 31 Afterwards, we ranked when comparing their binding affinities (kcal mol À1 ) of QPLD leads against pre-existing inhibitors (positive controls) as the best decisions to adaptable docking.…”
Section: Quantum Mechanics and Molecular Mechanics (Qm/ Mm) In Dockinmentioning
confidence: 99%
“…It is now well recognized that the accuracy of electronic charges and environmental polarization play a crucial role in ligand-protein docking (Illingworth et al, 2008;Park et al, 2013). A number of studies have indicated that recalculating atomic charges by the hybrid quantum mechanical/molecular mechanical (QM/MM) method can significantly improve the accuracy of the prediction of docking poses (Du et al, 2011;Cho et al, 2005;Cho & David, 2010).…”
Section: Introductionmentioning
confidence: 99%